DNA aptamer-based dual-responsive nanoplatform for targeted MRI and combination therapy for cancer. Issue 7 (31st January 2022) - Zhao, Mingming; Song, Xiaoxi; Lu, Jiahui; Liu, Siwen; Sha, Xuan; Wang, Qi; Cao, Xu; Xu, Kai; Li, Jingjing
Abstract : A glutathione (GSH) and adenosine-5′-triphosphate (ATP) dual-sensitive nanoplatform was designed for controlled drug release and activatable MRI of tumors based on DNA aptamer and manganese dioxide (MnO2 ) nanosheets. Abstract : Accurate drug delivery is a common topic, and it has always been an aim that scientists strive to achieve. To address this need, multifunctional and stimulus-sensitive nanoplatforms have attracted significant attention. Here we fabricated a glutathione (GSH) and adenosine-5′-triphosphate (ATP) dual-sensitive nanoplatform for controlled drug release and activatable MRI of tumors based on DNA aptamer and manganese dioxide (MnO2 ) nanosheets. Cleverly utilizing the DNA tunability, AS1411 aptamer which binds nucleolin, a protein specifically expressed on tumor-associated endothelial cells, was designed with ATP aptamer and its cDNA to load the anticancer drug, doxorubicin (Dox). The formed DNA-Dox complex was delivered to the tumor region with the help of MnO2 nanosheets and AS1411 aptamer. Then, the on-demand drug release in tumor cells was realized with the co-effect of the ATP aptamer and GSH reduction. It was found that without the structure of the MnO2 nanosheets being broken by GSH, Dox almost could not be released even in the presence of ATP. Similarly, without ATP, Dox was still maintained in the duplex even with GSH. Further combining the MRI ability and chemodynamic therapy of the produced Mn 2+, an improved effect of the inhibition of tumor growth and imaging was achieved. Our designed DNA aptamer-based dual-responsive nanoplatform can realize the targeted drug delivery and MRI of breast tumor cells both in vitro and in vivo .